Media convergence: lessons and questions from the Peruvian experience - Villanueva-Mansilla, Eduardo (2017)
Discussion on convergence, represented in a variety of academic fields related to communication, has not included production and consumption of content, notwithstanding the relative abundance of references to convergence in Peruvian business and government papers. This is addressed by drafting a definition of convergence analyzing its specific manifestation, trying to generalize how it affects the viability of media industries and the definition of communication policy. Models of convergence are analyzed and an interpretation that helps to understand convergence as a social and cultural phenomenon is proposed.